2019
DOI: 10.1016/j.eucr.2019.100886
|View full text |Cite
|
Sign up to set email alerts
|

One stage rotation flap scrotoplasty and orchidopexy for the correction of ectopic scrotum: A case report

Abstract: Ectopic scrotum (ES) is a particularly rare congenital malformation of the scrotum and commonly associated with other congenital malformations. A 2-year-old boy was presented with ectopic scrotum, low lesion imperforate anus, spina bifida and pubic diastasis since birth. There are various surgical methods available to be discussed in the management of ES. We performed correction of the ectopic scrotum and concomitant bilateral orchidopexy in one stage of surgery. This procedure is relatively simpler to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…ES and concurrent ectopic testes are the results of defective gubernaculum formation, which can be caused by mechanical, genetic, chromosomal, or teratogenic damage. Rare ectopias can be caused by abnormal migration or premature fission of the labioscrotal swellings (2,12,14,15). Reviewing the literature, we found that most ES were associated with other congenital malformations, but a few of them complicated with VATER/VACTERL syndrome were reported.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…ES and concurrent ectopic testes are the results of defective gubernaculum formation, which can be caused by mechanical, genetic, chromosomal, or teratogenic damage. Rare ectopias can be caused by abnormal migration or premature fission of the labioscrotal swellings (2,12,14,15). Reviewing the literature, we found that most ES were associated with other congenital malformations, but a few of them complicated with VATER/VACTERL syndrome were reported.…”
Section: Discussionmentioning
confidence: 91%
“…Ectopic scrotum (ES), commonly accompanied by other congenital malformations, is a kind of congenital scrotal anomaly. Mainly found in the inguinal, suprainguinal, infrainguinal, or perineal area, ES can occur anywhere from the inguinal canal and the perineum to the middle of the thigh (1)(2)(3)(4). Depending on the relative position of the penis and scrotum, penoscrotal transposition can be classified into incomplete transposition and complete transposition.…”
Section: Introductionmentioning
confidence: 99%
“…Various surgical techniques have been described, from hemiectopic scrotum removal and testis mobilization towards the opposite hemiscrotum, to Z-plasties and cutaneous rotation flaps (8) . I. Wahyudi et al recently published a one-stage scrotoplasty with rotation flap, with good results (9) . M.E.…”
Section: Discussionmentioning
confidence: 99%
“…This surgery is relatively straightforward and results in a pleasing cosmetic outcome. 10, 11 The limitation of this study is that the etiology of giant lymphedema remains unknown, whether caused by radiation, malignancy or congenital.…”
Section: Case Reportmentioning
confidence: 97%